The evaluation of mast cells of rat urinary bladder under stress conditions - (:unkn) unknown (My University, 1997)
Objective: Stress, is associated with many diseases of unknown etiology. This study demonstrates the effects of stress on distribution of mast cells of rat urinary bladder. Methods: Three experimental groups were designed as control, stress and recovery. Mast cells (MCs) in both mucosa and detrusor of the urinary bladder were both morphologicaly and quantitatively examined. Results: The statistical analyses showed a significant increase in the number of mast cells in the mucosa (p < 0.001) of the stress group when compared with the control group. Conclusion: The increase in the number of mast cells and the highly degranulated mast cell morphology in stress conditions were in accordance with the histopathological findings of many diseases of unknown etiology such as Interstitial Cystitis (IC), neurogenic bladder disease and bladder cancer.
Keywords: Experimental stress; Mast cell; Urinary bladder